Recent genome resequencing paraded COBRA-Like gene family roles in abiotic stress and wood formation in Poplar - Sajjad, Muhammad; Ahmad, Adeel; Riaz, Muhammad Waheed; Hussain, Quaid; Yasir, Muhammad; Lu, Meng‐Zhu (Frontiers in Plant Science, 2023)
A cell wall determines the mechanical properties of a cell, serves as a barrier against plant stresses, and allows cell division and growth processes. The COBRA-Like (COBL) gene family encodes a putative glycosylphosphatidylinositol (GPI)-anchored protein that controls cellulose deposition and cell progression in plants by contributing to the microfibril orientation of a cell wall. Despite being studied in different plant species, there is a dearth of the comprehensive global analysis of COBL genes in poplar. Poplar is employed as a model woody plant to study abiotic stresses and biomass production in tree research. Improved genome resequencing has enabled the comprehensive exploration of the evolution and functional capacities of PtrCOBLs (Poplar COBRA-Like genes) in poplar. Phylogeny analysis has discerned and classified PtrCOBLs into two groups resembling the Arabidopsis COBL family, and group I genes possess longer proteins but have fewer exons than group II. Analysis of gene structure and motifs revealed PtrCOBLs maintained a rather stable motif and exon–intron pattern across members of the same group. Synteny and collinearity analyses exhibited that the evolution of the COBL gene family was heavily influenced by gene duplication events. PtrCOBL genes have undergone both segmental duplication and tandem duplication, followed by purifying selection. Promotor analysis flaunted various phytohormone-, growth- and stress-related cis-elements (e.g., MYB, ABA, MeJA, SA, AuxR, and ATBP1). Likewise, 29 Ptr-miRNAs of 20 families were found targeting 11 PtrCOBL genes. PtrCOBLs were found localized at the plasma membrane and extracellular matrix, while gene ontology analysis showed their involvement in plant development, plant growth, stress response, cellulose biosynthesis, and cell wall biogenesis. RNA-seq datasets depicted the bulk of PtrCOBL genes expression being found in plant stem tissues and leaves, rendering mechanical strength and rejoinders to environmental cues. PtrCOBL2, 3, 10, and 11 manifested the highest expression in vasculature and abiotic stress, and resemblant expression trends were upheld by qRT-PCR. Co-expression network analysis identified PtrCOBL2 and PtrCOBL3 as hub genes across all abiotic stresses and wood developing tissues. The current study reports regulating roles of PtrCOBLs in xylem differentiating tissues, tension wood formation, and abiotic stress latency that lay the groundwork for future functional studies of the PtrCOBL genes in poplar breeding.